Clinical Outcomes of the Michigan Cranial Reshaping Orthosis. Issue 4 (October 2015) - Peethambaran, Ammanath; Foster, Alicia; Hickey, Kevin; Patterson, Rebecca
<x xml:space="preserve">Abstract</x> ABSTRACT Introduction: Infants treated for positional cranial asymmetry involving plagiocephaly, brachycephaly, and scaphocephaly are often treated with cranial reshaping orthotic helmets to encourage symmetrical cranial growth. The Michigan Cranial Reshaping Orthosis is a bivalve helmet that accommodates overall cranial growth during the therapy period while still directing cranial growth toward the desired areas. This design differs from standard one-piece helmets that allow limited volume for overall cranial growth. This study examines the efficacy and success rate of this low-profile design. Materials and Methods: Visual inspection and manual measurements taken throughout the helmet therapy period, using a flexible tape measure and an AP-ML gauge, indicate significant cranial asymmetry correction. However, measurement inconsistencies due to soft tissue compression and clinician technique may limit the accuracy of outcome measures. Seventy subjects treated for plagiocephaly and/or brachycephaly with the Michigan Cranial Reshaping Orthosis were identified in this retrospective study. Data were compiled from Omega Tracer (Ohio Willow Wood Company, Mount Sterling, OH, USA) computer-aided design clinical database of three-dimensional cranial scans taken before and after helmet therapy. Cranial helmet therapy treatment timeline was verified through the electronic medical record database. Cranial landmarks were defined on each three-dimensional image. Measurements between defined points were compared on the initial assessment scanned image and the final discharge scanned image for each patient. Results: Comparison of initial and final three-dimensional scans showed improved symmetry in the relevant measures of cranial vault asymmetry index (CVAI) and cephalic ratio (CR) in 84.3% of subjects. Children in the plagiocephaly-only group showed 28.8% improvement in CVAI. Although sample size was low, children in the brachycephaly-only group showed 4.66% improvement in CR. Children in the combined plagiocephaly/brachycephaly group showed 41.4% improvement in CVAI and 2.60% improvement in CR. Overall, a 33.5% in CVAI and 2.10% improvement in CR were seen. These results are comparable to other studies of remolding helmet efficacy. Conclusions: The data in the present study, therefore, support the use of the Michigan Cranial Reshaping Orthosis as a viable option in the treatment of plagiocephaly and/or brachycephaly when the primary method of treatment is utilization of a cranial remolding helmet.